Effects of face masks and ventilation on the risk of SARS-CoV-2 respiratory transmission in public toilets: a quantitative microbial risk assessment. (11th February 2022) - Denpetkul, Thammanitchpol; Pumkaew, Monchai; Sittipunsakda, Oranoot; Leaungwutiwong, Pornsawan; Mongkolsuk, Skorn; Sirikanchana, Kwanrawee
Abstract: Public toilets may increase the risk of COVID-19 infection via airborne transmission; however, related research is limited. We aimed to estimate SARS-CoV-2 infection risk through respiratory transmission using a quantitative microbial risk assessment framework by retrieving SARS-CoV-2 concentrations from the swab tests of 251 Thai patients. Three virus-generating scenarios were investigated: an infector breathing, breathing with a cough, and breathing with a sneeze. The infection risk (95th percentile) was as high as 10 −1 with breathing and increased to 1 with a cough or a sneeze. No significant gender differences for toilet users (receptors) were noted. The highest risk scenario, namely breathing with a sneeze, was further evaluated for risk mitigation measures. Mitigation to a lower risk under 10 −3 succeeded only when the infector and the receptor both wore N95 respirators or surgical masks. Ventilation of up to 20 air changes per hour (ACH) did not decrease the risk. However, an extended waiting time of 10 min between an infector and a receptor resulted in approximately 1.0-log10 further risk reduction when both wore masks with the WHO-recommended 12 ACH. The volume of expelled droplets, virus concentrations, and receptor dwell time were identified as the main contributors to transmission risk. HIGHLIGHTS: The use of public toilets poses a risk of SARS-CoV-2 respiratory transmission. No gender differences in risk by counteracting dwell times and inhalation rates. Ventilation alone did not reduce risk at 20 ACH with immediate receptor entrance. 10-min waiting time further mitigated risks beyond face masks at 12 ACH ventilation. N95 and surgical masks offer the most effective risk mitigation to toilet users. Graphical Abstract